2021
DOI: 10.1097/md.0000000000025608
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine injection for promoting blood circulation and removing blood stasis in treating angina pectoris of coronary heart disease

Abstract: Background: As a common cardiovascular disease, the morbidity and mortality of coronary heart disease (CHD) are increasing year by year. In recent years, many RCTs have proved that compared with conventional therapy, the combination of TCMIs for promoting blood circulation and removing blood stasis can improve clinical efficacy. However, there is still a lack of direct comparative study between different kinds of TCMIs. Therefore, based on the NMA, this study compares the curative effects of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…It also has anti-platelet aggregation effects and protects the vascular endothelium. 20 Recent studies used Gualou Xiebai Banxia Decoction to treat 31 cases of chronic heart failure of coronary heart disease with phlegm rubidium-blocked qi stagnation and blood stasis, with satisfactory clinical efficacy and a total effective rate of 90.3%. 21 Another study treated 226 patients with stable angina pectoris and type-2 diabetes by trichosanthis peel injection and found that angina pectoris symptoms and hemorheology indices in the experimental group were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has anti-platelet aggregation effects and protects the vascular endothelium. 20 Recent studies used Gualou Xiebai Banxia Decoction to treat 31 cases of chronic heart failure of coronary heart disease with phlegm rubidium-blocked qi stagnation and blood stasis, with satisfactory clinical efficacy and a total effective rate of 90.3%. 21 Another study treated 226 patients with stable angina pectoris and type-2 diabetes by trichosanthis peel injection and found that angina pectoris symptoms and hemorheology indices in the experimental group were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that trichosanthis peel fructus extract can dilate coronary arteries, increase coronary blood flow, improve myocardial ischemia symptoms, reduce myocardial contractility, slow heart rate, reduce myocardial oxygen consumption and significantly reduce serum cholesterol, low‐density lipoprotein and triacylglycerol, thus playing a role in lowering blood lipids. It also has anti‐platelet aggregation effects and protects the vascular endothelium 20 . Recent studies used Gualou Xiebai Banxia Decoction to treat 31 cases of chronic heart failure of coronary heart disease with phlegm rubidium‐blocked qi stagnation and blood stasis, with satisfactory clinical efficacy and a total effective rate of 90.3% 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Mailuoning injection, the composite traditional Chinese medicine preparation, has been clinically recognized for its ability to enhance blood flow, prevent clot formation, nourish yin, and dissipate heat 11,12 . It comprises a blend of potent ingredients including Achyranthes bidentata, honeysuckle, Radix Scrophulariae, and Dendrobium, each offering unique therapeutic benefits ranging from improving circulation and reducing inflammation to nourishing bodily fluids and alleviating pain 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The NEB can be determined using plasma thresholds of β-hydroxybutyrate, non-esterified fatty acids and glucose ( Macrae et al, 2019 ; Churakov et al, 2021 ). Additionally, blood stasis, defined by sub-optimal blood flow rather than by thrombosis ( Huang et al, 2021 ), happens broadly during female pregnancy and recovers spontaneously a few days after delivery. However, insufficient Qi to provide power for motion may result in continued postpartum blood stasis ( Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%